2019
DOI: 10.1186/s13014-019-1425-7
|View full text |Cite
|
Sign up to set email alerts
|

Intrafractional 6D head movement increases with time of mask fixation during stereotactic intracranial RT-sessions

Abstract: BackgroundThe present study investigates the intrafractional accuracy of a frameless thermoplastic mask used for head immobilization during stereotactic radiotherapy. Non-invasive masks cannot completely prohibit head movements. Previous studies attempted to estimate the magnitude of intrafractional inaccuracy by means of pre- and postfractional measurements only. However, this might not be sufficient to accurately map also intrafractional head movements.Materials and methodsIntrafractional deviation of mask-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…18,[31][32][33][34][35] It was reported that these systems can correct the 6DoF setup errors with accuracy within approximately 0.5°and 0.5 mm. [34][35][36] Therefore, if patient setup corrections < 0.5°and 0.5 mm are not possible due to device-specific uncertainty, it would be prudent not to use SIVMAT when the GTV diameter is as small as 1.5 cm. When the likely patient localization set up error is no more than 0.5°and 0.5 mm, the maximum distances at which the clinical PTV margin satisfied the 5% tolerance values were 5.5 cm for 1.5 cm diameter, 11.9 cm for 2 cm diameter and 17.5 cm for 3 cm diameter GTV.…”
Section: Discussionmentioning
confidence: 99%
“…18,[31][32][33][34][35] It was reported that these systems can correct the 6DoF setup errors with accuracy within approximately 0.5°and 0.5 mm. [34][35][36] Therefore, if patient setup corrections < 0.5°and 0.5 mm are not possible due to device-specific uncertainty, it would be prudent not to use SIVMAT when the GTV diameter is as small as 1.5 cm. When the likely patient localization set up error is no more than 0.5°and 0.5 mm, the maximum distances at which the clinical PTV margin satisfied the 5% tolerance values were 5.5 cm for 1.5 cm diameter, 11.9 cm for 2 cm diameter and 17.5 cm for 3 cm diameter GTV.…”
Section: Discussionmentioning
confidence: 99%
“…With the advances in image guidance, frameless fixation-based SRS or SRT has been clinically implemented [3][4][5][6][7]. However, it has been shown that frameless fixation allows for larger motion when compared to frame-based fixation [8][9][10]. Thus, it becomes important to ensure sensitive and precise motion management to guide frameless SRS and SRT treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Although cumulatively more time is spent on patient setup and verifying initial positional accuracy with multifaction regimens compared to single fraction regimens, beam‐on time for each fraction is shorter with a multifraction regimen than a single‐fraction regimen, assuming the same dose rate. Patient motion during beam‐on time increases with increasing treatment time and degrades the positional accuracy of treatment, highlighting the importance of minimizing beam‐on time with each treatment session 24‐26 . Thus, frameless linac‐based SRS delivered over multiple fractions is an attractive treatment option for the management of JTPs in these patients, and this series lends support to this treatment strategy with evidence of long‐term efficacy.…”
Section: Discussionmentioning
confidence: 71%
“…Given the elderly and frail patient population often referred for SRS for JTPs, immobilization for a prolonged period of time may be intolerable and may require sedation. Additionally, longer treatment time is associated with increased intrafraction patient motion, which may lead to decreased treatment accuracy 24‐26 . Improved imaging modalities and image‐guided techniques over the past few decades have allowed for linac‐based SRS to be delivered over multiple fractions of shorter individual treatment duration and without use of a rigid stereotactic headframe.…”
Section: Introductionmentioning
confidence: 99%